Against the Flow: The Colonisation of the Lesotho Highlands by Freshwater Limpets - Sands, Arthur F.; Riedel, Frank; Gummersbach, Venise S.; Albrecht, Christian (Frontiers in Environmental Science, 2022)
To date, limited research has taken place on the evolutionary history of biodiversity in the high-altitude zone of southern Africa, particularly the Lesotho Highlands. The few studies that do exist point to similar high-altitude zones being either prolific museum (i.e. refugia and cradle) for cold-evolved species of southern Africa or sink for temperate species post the last glacial maximum, yet the role this zone has played for freshwater biodiversity is unknown for almost all freshwater taxa. In this study, we address this lack of knowledge by looking at the phylogeography of the freshwater limpet genus, Burnupia, across its southern and eastern African range, but particularly focusing on the Lesotho Highlands. We used COI data to reconstruct the evolutionary history of the genus, quantify phylogenetic species diversity, test both isolation by distance (IBD) and by elevation (IBE) and model ancestral area estimation “in” and “out” of the Highlands to determine: a) the diversity and endemicity of Burnupia spp. in the Highlands in comparison to the broader southern African region and b) when did the colonisation of the Highlands happen. Our results showed that at least two of the nine southern African phylogenetic species delimited occur in the Highlands (which appears average for the geographical extent of this area in comparison to the broader southern African region) and that the genus has been present in the Lesotho Highlands from around the Middle to Late Pleistocene transition. Moreover, we found the endemicity of at least one of the two Highland species, supported by weak but significant IBD and IBE in Burnupia, as such we favour the notion that the Highlands are likely an important haven for cold-evolved species. As our results also generated a lot of data useful for Burnupia systematics we discuss some taxonomic implications of our findings.